Faktor-Faktor yang Mempengaruhi Tingkat Produktivitas Usahatani Kedelai di Kabupaten Tasikmalaya: Factors Affecting the Productivity Level of Soybean Farming in Tasikmalaya Regency - Candra Nuraini; Dina Agustina; Zulfikar Noormansyah (Research and Social Study Institute (RESSI), 2022)
In order to achieve self-sufficiency in soybeans, one of the efforts made is to increase soybean production and productivity. So that a study is needed that aims to analyze the factors that affect the productivity of soybean farming. This research was conducted in Tasikmalaya Regency which was determined by purposive sampling. Specifically, the research location is in two districts, namely Pancatengah District and Jamanis District, with consideration of representing two different agro-ecosystems (lowlands and highlands). This research uses a survey method. Analysis approach with multiple linear regression. The results showed that the factors that simultaneously affected the productivity of soybean farming were experience, number of family dependents, education, motivation, and land/agro-ecosystem conditions. While the factors that partially influence, among others: experience, motivation, and condition of the land/agro-ecosystem. The factors that do not influence partially are the number of family dependents and education.